Human resource management - Dessler, Gary, 1942-; Varkky, Biju. (Hoboken, NJ ; India : Pearson, 2024)
"Human Resource Management , 17th edition, provides students in human resource management courses and practicing managers with a full and practical introduction to the latest human resource management concepts and techniques in a highly readable and understandable form. As this new edition goes to press, I feel even more strongly than I did when I wrote the first edition that all managers-not just HR managers-need a strong foundation in HR/personnel management concepts and techniques to do their jobs effectively. You will therefore find an emphasis here on practical material you need to perform your day-to-day management responsibilities, even if you never spend a day as a human resource manager. To ensure a smooth transition for adopters from the 16th to this 17th edition, this edition's 18 chapter table of contents and the outline of all but Chapter 1 are basically as they were in the 16th edition. Therefore, in terms of teaching, the topic flow is about the same as the 16th edition. However, embedded in each chapter's paragraphs are dozens of new topics, practical examples, and research insights, all accompanied by hundreds of new references. I particularly examined every word and line in this edition, making dozens and dozens of "fine-tuning" improvements which, while possibly invisible to the casual reader, further improve the book's already high readability"--
Includes bibliographical references and index.
BBS
Karim International
Keywords: Personnel management; Management